Covid-19 Pandemic and the Digital Revolution in Academia and Higher Education: an Empirical Study - S. Mahabub Basha; M Kethan (Green Publisher Indonesia, 2022)
While learning online during the pandemic students faced so many problems difficulties and challenges with respect to the stress worry anxiety technology adaptability course content delivery and explanation in the digital transformation from a physical classroom learning to an online mode amidst pandemic. This research aims to explore challenges facing students using a student online survey and data was analyzed using SPSS for student’s online learning experiences amidst the pandemic which was handled adequately. Extraction of common factor variances from measure sets for getting prominent factors to measure the transformational shift from offline to online digital learning was done using Exploratory Factor Analysis. Sampling Adequacy Measure test of KMO a correlation matrix which indicates whether the variables are unrelated in the Bartlett’s Sphericity test in which the level of significance gives the test result showed in the present study that significant relationships exists among variables and there is high correlation. Principle Component Analysis (PCA) with Varimax rotation used for challenges showed inter-correlation and a significant relationship of students challenges faced in digital mode with significant P value at 5% level of significance. Regression analysis testing H0 variable relationship with one or more variables revealed significant constant value with psychological, technological and personal opinion as three representative factors found to be significant so the H0 stands rejected